Brain Function Changes Induced by Intermittent Sequential Pneumatic Compression in Patients With Stroke as Assessed by Functional Near-Infrared Spectroscopy. Issue 9 (31st May 2021) - Xie, Hui; Xu, Gongcheng; Huo, Congcong; Li, Wenhao; Zhao, Haihong; Lv, Zeping; Li, Zengyong
Abstract: Objective: Intermittent sequential pneumatic compression (ISPC) can effectively promote cerebral perfusion and collateral blood supply in patients with stroke. However, the effects of ISPC on cerebral oscillations are still unclear. Methods: The tissue concentration of oxyhemoglobin and deoxyhemoglobin oscillations were measured by functional near-infrared spectroscopy under resting and ISPC conditions in 27 right-handed adult patients with stroke. Five characteristic frequency signals (I, 0.6–2 Hz; II, 0.145–0.6 Hz; III, 0.052–0.145 Hz; IV, 0.021–0.052 Hz; and V, 0.0095–0.021 Hz) were identified using the wavelet method. The wavelet amplitude (WA) and laterality index (LI) were calculated to describe the frequency-specific cortical activities. Results: The ISPC state of patients with ischemic stroke showed significantly increased WA values of the ipsilesional motor cortex (MC) in the frequency intervals III ( F 37 = 8.017), IV ( F 37 = 6.347), and V ( F 37 = 5.538). There was no significant difference in the WA values in the ISPC state compared with the resting state in patients with hemorrhagic stroke. Also, the LI values of the prefrontal cortex and MC in patients decreased more obviously in the ISPC state than in the resting state despite no significant difference. Conclusion: The significantly increased WA values in the frequency intervals III, IV, and V in the MC of patients with ischemic stroke might be related to cortical activity in the MC in addition to increased cerebral perfusion. The decreased LI values in the prefrontal cortex and MC indicated that the ISPC may have had a positive effect on the functional rehabilitation of these regions. Impact: This study provides a method for assessing the effects of ISPC on cerebral oscillations, and the results benefit the optimization of ISPC parameters in personalized treatment for the functional recovery of patients with stroke.